Parenting styles and teacher interaction on self-regulated learning and academic performance - Ariana Isufi; Mytaher Haskuka (International Journal of Adolescence and Youth)
The importance of parenting styles and teacher interaction on self-regulated learning (SRL) and academic performance is well documented. This study aimed to identify the correlation between parenting styles and interaction with teachers, with SRL in students and how these predict academic performance. The cross-sectional design research was conducted with 420 students selected using a random cluster sampling method. Data collection was carried out in classrooms through self-administered questionnaires. The study’s results show that the authoritative parenting style and teachers’ cooperative behaviour were positively correlated with SRL strategies. There was a negative correlation between the tolerant parenting style and teachers’ dominance behaviour with SRL strategies. Parenting styles and interaction with teachers accounted for 34.9% of the variance in SRL among adolescents. SRL was positively correlated with academic success. Considering Kosovo students’ low educational outcomes, these findings provide insights for a shift towards more parent-teacher interactive education.